The role of Infertility-related psychological inflexibility in the relationship between infertility-related stress and depressive symptoms in women with infertility - Cardoso, Beatriz (2021)
Background and Aim: Introduction: Infertility is a medical and social condition that impacts people’s lives at the marital, family, social and financial levels. Several studies point to comorbidity between psychopathology and infertility, and people facing the demands of infertility may use maladaptive mechanisms of emotion regulation translated into psychological inflexibility. Objectives: This current study aimed to explore the mediating role of infertility-related psychological inflexibility in the relationship between infertility-related stress and depressive symptoms in women presenting an infertility diagnosis and pursuing infertility medical treatment. In addition, as a secondary aim, the associations between the time since diagnosis and the study variables were examined. Methods: A cross-sectional study was conducted on a sample of 96 women recruited with the support of the Portuguese Fertility Association. Participants filled in online a set of self-report instruments. Sociodemographic and clinical data were collected, and standardized measures of infertility-related stress, depressive symptoms, and infertility-related psychological inflexibility were used. Results: The results demonstrated that the effect of infertility-related stress on depressive symptoms was .46, being totally mediated by infertility-related psychological inflexibility. Discussion: Difficulty in achieving a pregnancy is a painful life event that interferes with the goals and plans for building a family, which can lead to stress and depressive symptoms. The relationship between these symptoms seems to be influenced by the mechanism of infertility-related psychological inflexibility. Therefore, interventions such as Acceptance and Commitment Therapy and the Mindfulness-Based Program for Infertility may be particularly suitable for this population by integrating psychological inflexibility as a therapeutic target.